2017
DOI: 10.1002/cbin.10792
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products induce hepatocyte epithelial–mesenchymal transition via a ROS‐dependent, TGF‐β/Smad signaling pathway

Abstract: Epithelial-mesenchymal transition (EMT) occurs during the progression of liver fibrosis in response to chronic liver injury. However, the molecular mechanism underlying the regulation of hepatocyte EMT remains unclear. The aim of this study was to determine whether advanced oxidation protein products (AOPP) had an effect on hepatocyte EMT. The human L02 hepatocyte cell line and hepatocytes from normal Sprague-Dawley rats were challenged with AOPP treatment in both in vitro and in vivo studies. The expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
(58 reference statements)
2
16
0
Order By: Relevance
“…In the cytosol, it can act as a direct scavenger of ROS. In addition, previous studies revealed the role of ROS in EMT processes of hepatocytes [38][39][40]. In the present study, we also showed that melatonin suppressed ROS generation induced by TGF-β1 treatment and NAC, a well-known antioxidant, also effectively prevented TGF-β1-induced EMT.…”
Section: Discussionsupporting
confidence: 82%
“…In the cytosol, it can act as a direct scavenger of ROS. In addition, previous studies revealed the role of ROS in EMT processes of hepatocytes [38][39][40]. In the present study, we also showed that melatonin suppressed ROS generation induced by TGF-β1 treatment and NAC, a well-known antioxidant, also effectively prevented TGF-β1-induced EMT.…”
Section: Discussionsupporting
confidence: 82%
“…Immunohistochemical (IHC) analysis was performed as previously described [ 21 , 22 ]. Briefly, HCC and matched adjacent non-cancerous tissues were fixed in 4% paraformaldehyde, embedded in paraffin wax, and sectioned at 4-μm thickness.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the case of continuous activation of inflammatory response, the EMT process will also exist continuously, and eventually cause organ fibrosis[ 18 , 19 ]. Nowadays, although the role and regulation mechanism of EMT in CD intestinal fibrosis has not been fully understood, the transforming growth factor-β (TGF-β)/Smad/MAPK signaling pathway has been confirmed to play an important role in regulating EMT in organs such as lung, liver, kidney and so on[ 20 - 22 ]. Therefore, studying the role of EMT in the formation of intestinal fibrosis based on the TGF-β/Smad/MAPK signaling pathway, may provide a new target for the treatment of CD intestinal fibrosis.…”
Section: Introductionmentioning
confidence: 99%